2018
DOI: 10.1016/j.bbrc.2018.06.120
|View full text |Cite
|
Sign up to set email alerts
|

HDAC9 overexpression confers invasive and angiogenic potential to triple negative breast cancer cells via modulating microRNA-206

Abstract: Triple negative breast cancer (TNBC) is among the most aggressive breast cancer subtypes with poor prognosis. The purpose of this study is to better understand the molecular basis of TNBC as well as develop new therapeutic strategies. Our results demonstrate that HDAC9 is overexpressed in TNBC compared to non-TNBC cell lines and tissues and is inversely proportional with miR-206 expression levels. We show that HDAC9 selective inhibition blocked the invasion of TNBC cells in vitro and repressed the angiogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…The fact that the expression of miR-206 was significantly down-regulated in TNBC compared to non-TNBC strongly suggested its involvement in the development of more aggressive characteristics associated with TNBC subtype. These findings are in accordance with results of Salgadoa et al who also reported that TNBC tissues and cell lines expressed miR-206 less than non-TNBC equivalents [23]. Downregulation of miR-206 in TNBC have been linked with repression of cell migration via direct targeting of many proteins including actin-binding protein coronin 1C [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The fact that the expression of miR-206 was significantly down-regulated in TNBC compared to non-TNBC strongly suggested its involvement in the development of more aggressive characteristics associated with TNBC subtype. These findings are in accordance with results of Salgadoa et al who also reported that TNBC tissues and cell lines expressed miR-206 less than non-TNBC equivalents [23]. Downregulation of miR-206 in TNBC have been linked with repression of cell migration via direct targeting of many proteins including actin-binding protein coronin 1C [24].…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports have supported the role of miR-206 in the progression of many types of cancers [21]. Low levels of miR-206 expression have been correlated with tumor size and advanced pathological stage which suggested its use as a promising prognostic marker in breast cancer [22,23].…”
Section: Discussionmentioning
confidence: 90%
“…The protective effects of miR-206 on inhibition of cell proliferation and promotion of cell apoptosis have also been widely studied in various human diseases including knee articular osteoarthritis, prostate cancer, cervical cancer, triple negative breast cancer and etc. [37][38][39][40]. All these findings suggest the essential roles of miR-206 in the modulation of pathophysiology of human diseases including AMI.…”
Section: Discussionmentioning
confidence: 75%
“…The specific molecular mechanism is related to the direct regulation of proto-oncogene/tumor suppressor gene and ncRNA expression by HDAC9. The currently known tumor suppressor gene P53 [44], deacetylated forkhead box gene O1 (FoxO1) [48], sex determining region Y-box 9 protein (SOX9) [49] and transcriptional coactivator with PDZ-binding motif (TAZ) [50] are potential target genes of HDAC9; changes in HDAC9 expression affect the transcription of target genes, thereby activating downstream signaling pathways, such as those involving the oncogenes Ras, VEGF, MAPK and EGFR, to promote tumor cell proliferation [51]. HDAC9 has been rarely studied in the context of HCC; most publications have focused on its relationship with miRNA.…”
Section: Rbm8a (Y 14)mentioning
confidence: 99%